Effect of Form on Radiation Absorption in Ab Anbar Domes of Hot and Arid and Cold Climate Using Honeybee & ladybug Plugins - tohid shiri; Mohammad Didehban; Mohsen Taban (تحقیقات کاربردی علوم جغرافیایی, 2024)
In the past, architects in many parts of Iran had built traditional public buildings to create a community convenience and comfort. Ab Anbars are good example of this facility structures which they were suppose to collect water in rainy condition and keep it cool for use in dry condition of year espacialy in hot and arid climate. To study amount of radiation and heat absorption 2 Domes of Ab Anbar in Yazd (hot and arid climate) and 2 Domes of Ab Anbar in Qazvin (cold climate) were selected. In order to simulate the domes, they were first modeled in Revit software 2017, and then models were transferred to Rhino 5 software, using the honeybee & lady bug, and with the Energy plus Engine analysis of the received solar radiation and shading were done. In the analyzes, uniformity of the dimensions of the Ab Anbars domes were used, so that the optimum dome can be obtained in terms of receiving solar radiation and absorbing heat in the shadowed area. To equalize the domes, the absorption of the sun's radiation of each dome is divided by the amount of shadowing of the same dome.Radiation absorption in hottest day of the year in hat and arid climate and coldest day of year in cold climate were calculated using Energy Plus software Honeybee & ladybug Plugins. Result shows that amount of radiation is dependent to form of domes. During study day (14,16 and 18 o’clock ) 78, 71 and 64 percent of high rise Domes  is facing radiation while 93,81 and 64 percent of  low rise domes is facing radiation. From this results it can be concluded that high rise domes have better function in hot and arid climate and low rise domes have better function in cold climate in relation to radiation absorption.